Rapid response on facial psoriasis to bimekizumab: case series - Nicoletta Bernardini; Annunziata Dattola; Giacomo Caldarola; Diego Orsini; Chiara Assorgi; Alessandra D'Amore; Giulia Maretti; Antonio Giovanni Richetta; Ersilia Tolino; Nevena Skroza; Concetta Potenza (BioExcel Publishing Ltd, 2024)
Psoriasis is a chronic inflammatory disease that can affect any part of the body but, when it appears in certain areas, like the face, it can have a very significant psychological impact. Biologics, in particular IL-17 and IL-23 drug inhibitors, have shown relevant clinical efficacy in the management of psoriatic lesions in difficult-to-treat areas. In post hoc analysis of phase III trials in plaque psoriasis, bimekizumab has shown safety and complete clearance of high-impact areas. However, these studies did not focus on the effect of bimekizumab on facial lesions. Therefore, this case series represents the first clinical real-life experience of rapid and successful management of facial psoriasis with bimekizumab in six patients.